FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN SECARA ONLINE DI ONLINE SHOP LAZADA - Lina Aryani (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2016)
This study aimed to determine the product, price, trust, security, and service to online purchasing decision on the Lazada online shop. The samples in this study were 70 respondents who are buyer of Lazada online shop. The sample size in this study using roscoe formula that the decent sample size in the study is between 30 to 500. Methods of data collection by questionnaire. Data analysis using regressions analysis and hypotheses using t-statistics and f-statistics with a confidence level of 5%. The result of this research shows that partially product influences to online purchasing decision, price does not influences to online purchasing decision, trust influences to online purchasing decision, security does not influences to online purchasing decision, and service influences to online purchasing decision. Simultaneously all independent variables influences purchasing decision.